Evaluasi Kebijakan Pengentasan Kemiskinan di Kecamatan Kokap, Kabupaten Kulon Progo - Anggita Selewang; Jawoto Sih Setyono (Teknik PWK (Perencanaan Wilayah Kota), 2020)
Poverty is a condition of someone that trapped in a vicious cycle of poverty and does not have the ability to break the cycle. They need an intervention from the authorities, such as government policy, which can help someone get out of the poverty trap. Until 2018, Kokap District is still one of the biggest poverty pockets in the Special Region of Yogyakarta (DIY) ). Thus, further studies need to be done to assess the effectiveness of poverty alleviation policies implemented in Kokap District. The method used in this study is the Delphic Hierarchy Process (DHP). The Delphi method will be used to weight the evaluation criteria in evaluating poverty alleviation policies, while AHP is used to assess the importance of poverty alleviation policies. Weighting the policy evaluation criteria gives the result that the criteria for human assets and the sustainability of economic aspects of the poor are the criteria with the highest weight. While the assessment of the level of importance of the policy provides the result that social assistance policies are still a priority in Kokap District. In addition, this study found that the policy with a high and medium priority level is a policy whose implementation is integrated from the central government to regional governments.